A Model for the Departmental Quality Management Infrastructure Within an Academic Health System. (May 2017) - Mathews, Simon C.; Demski, Renee; Hooper, Jody E.; Biddison, Lee Daugherty; Berry, Stephen A.; Petty, Brent G.; Chen, Allen R.; Hill, Peter M.; Miller, Marlene R.; Witter, Frank R.; Allen, Lisa; Wick, Elizabeth C.; et al.
Abstract : As quality improvement and patient safety come to play a larger role in health care, academic medical centers and health systems are poised to take a leadership role in addressing these issues. Academic medical centers can leverage their large integrated footprint and have the ability to innovate in this field. However, a robust quality management infrastructure is needed to support these efforts. In this context, quality and safety are often described at the executive level and at the unit level. Yet, the role of individual departments, which are often the dominant functional unit within a hospital, in realizing health system quality and safety goals has not been addressed. Developing a departmental quality management infrastructure is challenging because departments are diverse in composition, size, resources, and needs. In this article, the authors describe the model of departmental quality management infrastructure that has been implemented at the Johns Hopkins Hospital. This model leverages the fractal approach, linking departments horizontally to support peer and organizational learning and connecting departments vertically to support accountability to the hospital, health system, and board of trustees. This model also provides both structure and flexibility to meet individual departmental needs, recognizing that independence and interdependence are needed for large academic medical centers. The authors describe the structure, function, and support system for this model as well as the practical and essential steps for its implementation. They also provide examples of its early success.